Probiotics advanced food and health applications - Brandelli, Adriano (London Academic Press, imprint of Elsevier, 2022)
Probiotics: Advanced Food and Health Applications presents the functional properties and advanced technological aspects of probiotics for food formulation, nutrition, and health implications. Specifically, the book addresses the fundamentals of probiotics, from their discovery to actual developments, the microbiological aspects of the main genus showing probiotic properties, the natural occurrence of probiotic strains in foods, the development of nutraceuticals based on probiotics, and the relationship of probiotics to health. The book also includes a discussion on regulatory aspects. This book is an excellent resource for food scientists, nutritionists, dieticians, pharmaceutical scientists, and others working with probiotics or studying related fields.
1. An introduction to probiotics -- 2. Prebiotics and synbiotics -- 3. Microorganisms with food applications as probiotics -- 4. Beneficial microbes from human and animal intestines -- 5. High-throughput technologies in probiotics science -- 6. Probiotics in milk and dairy foods -- 7. Probiotics in meat products -- 8. Development of high-protein whey-based beverage rich in probiotics -- 9. Effect of food ingredients on susceptible gut indigenous bacteria -- 10. Encapsulation of probiotics -- 11. Prospective applications of probiotics and prebiotics in foods -- 12. Food-gut microbiota interactions -- 13. Food-based probiotics: functional dietary ingredients -- 14. Probiotics in sports nutrition -- 15. Impact of probiotic supplementation and the role of gut microbiome in obesity -- 16. Immunomodulatory and anti-inflammatory mechanisms of probiotics -- 17. Probiotics and intestinal health -- 18. Probiotics and urogenital health -- 19. Probiotics and skin health -- 20. Probiotics in the management of diabetes -- 21. Probiotics in pediatrics -- 22. Probiotics and the gut-brain axis -- 23. Probiotics and the gut-liver axis -- 24. Next generation probiotics.
Includes bibliographical references and index.
Keywords: Probiotics